Ammonia Selectivity Over Acetone by Viscosity Modulation of Silicone Oil Filter for Diagnosing Liver Dysfunction. (9th December 2020) - Agarwal, Ashish; Rai, Sujeet Kumar; Lin, Yu-Chen; Patnaik, Rakesh Kumar; Yeh, J. Andrew
Abstract : Breath ammonia is an important biomarker linked to liver malfunction. Acetone is the most abundant compound in the breath, acts as major interference for selective detection of ammonia gas. Here, a novel method based on viscosity modulation of the silicone oil absorbent is reported for selectivity improvement of ammonia over acetone gas. ATD-GC-MS and T201 ammonia analyzer are used to measure the absorption of acetone and ammonia respectively into the silicone oil. The absorption of ammonia and acetone gas is measured in different absorbent viscosities at a constant flow rate (50 cc min −1 ). Absorption results of ammonia are 7.37%, 16.3%, and 17.1% and acetone absorption results are 35%, 68%, and 78% respectively into 500 cSt, 100 cSt, and 20 cSt viscous silicone oil at room temperature. More bubbles of smaller diameter are formed at a lower viscosity, increases the contact time of the gas with absorbent. Consequently, the absorption of acetone into silicone oil at lower viscosity increases as compared to ammonia. The absorption of acetone is about 4.6-fold higher than the ammonia. Hence, it proves to be an effective technique for enhancing selectivity. This novel concept can be incorporated with any sensor for portable breath ammonia sensing in the detection of liver dysfunction.